Award for the World Hearing Grant (WHO) - Binos, Paris (My University, 2026)
Your application to the World Hearing Day Small Grants Program has been selected for this award and recognition. Your outstanding application was selected from almost 400 applications for this prestigious award. Each grant application was reviewed and selected by our panel of global hearing health experts. Your planned activities support the 2025 World Hearing Day theme of “Changing Mindsets: Empower yourself! Make ear & hearing care a reality for all!”
Keywords: Education